Pregnancy‐associated haemolytic anaemia: A cause not to be forgotten. (March 2023) - Creeper, Katherine; Graham, Dorothy
Anaemia in pregnancy is common, however, only a few cases of pregnancy-associated autoimmune haemolytic anaemia have been documented. Typically, such cases involve a positive direct antiglobulin test and have the potential to cause haemolytic disease of the fetus and newborn. Rarely, no autoantibodies are detected. We report two cases of direct antiglobulin test negative haemolytic anaemia occurring in multiparous women with no cause found. Both women had a haematological response to corticosteroid therapy and delivery.